Programa en habilidades emocionales para la vida como prevención al suicidio en los estudiantes del Colegio German Pardo - Rojas Masmela, Laura Daniela (Universidad Antonio Nariño, 2024)
Suicide is a far-reaching and complex issue that affects individuals, families, and communities as a whole. It is linked to numerous elements, such as mental health conditions, moments of tension, biological bases and traumatic experiences. This action implies that an individual deliberately decides to end his own life. It is a multifaceted issue that encompasses social, cultural and family aspects.